Cytokine-Mediated Crosstalk Between Keratinocytes and T Cells in Atopic Dermatitis - Humeau, Mélanie; Boniface, Katia; Bodet, Charles (Frontiers in Immunology, 2022)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by barrier dysfunction, dysregulated immune response, and dysbiosis with increased Staphylococcus aureus colonization. Infiltration of various T helper cell subsets into lesional skin and subsequent cytokine release are a hallmark of AD. Release of cytokines by both T cells and keratinocytes plays a key role in skin inflammation and drives many AD features. This review aims to discuss cytokine-mediated crosstalk between T cells and keratinocytes in AD pathogenesis and the potential impact of virulence factors produced by Staphylococcus aureus on these interactions.